Preparation and solid state characterisation of chlorothiazide sodium intermolecular self assembly suprastructure - TAJBER, LIDIA; MC CABE, THOMAS; HEALY, ANNE MARIE; O'BRIEN, JOHN EUGENE; CORRIGAN, OWEN; PALUCH, KRZYSZTOF (Elsevier, 2010)
Chlorothiazide (CTZ), unlike other thiazide diuretics, can form salts. An injectable formulation containing the sodium salt is available; however neither the physicochemical characteristics of the salt nor its solid state form have been previously reported. This work reports on the crystal structure of chlorothiazide sodium. The structure was investigated by single crystal X-ray and nuclear magnetic spectroscopy (NMR) analyses and compared to chlorothiazide, while the solid state characteristics were assessed by thermal analysis, powder X-ray diffraction, infrared spectroscopy, dynamic moisture sorption and solubility analysis. The crystal structure of chlorothiazide sodium was determined to be triclinic; the crystal space group type was P-1. Chlorothiazide sodium presented a self-assembly polymeric-type suprastucture, where the unit cell comprised two chlorothiazide molecules bonded together with sodium cations through the water bridges. The coordinate centre comprised the following: (CTZ)3?(H2O)?Na(H2O)2Na?(H2O)?(CTZ)3. The crystalline material was determined to be a monosodium dihydrate, stable in the range of 10-90% relative humidity (RH) at 25 ?C. Additional processing of the salt resulted in a crystalline anhydrous form which was stable in the range 0-20% RH at 25 ?C. The aqueous solubility of the chlorothiazide sodium dihydrate at 37 ?C was found to be approximately 400-fold higher than that of chlorothiazide, which may present biopharmaceutical advantages for the salt compared to the non-salt form.
PUBLISHED
Keywords: Medicinal chemistry; thiazide diuretics; chlorothiazide sodium